2015
DOI: 10.3340/jkns.2015.57.5.376
|View full text |Cite|
|
Sign up to set email alerts
|

Delayed Pneumocephalus Following Fluoroscopy Guided Cervical Interlaminar Epidural Steroid Injection: A Rare Complication and Anatomical Considerations

Abstract: Cervical epidural steroid injection is indicated for radicular symptoms with or without axial neck pain. Complications are rare but can be serious. Here, we report the case of a 54-year-old man with cervical radicular pain who was treated with cervical epidural steroid injection. Injection was administered twice under fluoroscopic guidance with the loss-of-resistance technique using air to confirm the epidural space. After the second procedure, the patient complained of severe persistent headache and was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recent measurements of dural thickness have also demonstrated that the posterior dura varies in thickness, and that the thickness of the dura at a particular spinal level is not predictable within an individual or between individuals [ 16 ]. Dural perforation in a thick area of dura may be less likely to lead to a CSF leak than a perforation in a thin area, and may explain the unpredictable consequences of a dural perforation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent measurements of dural thickness have also demonstrated that the posterior dura varies in thickness, and that the thickness of the dura at a particular spinal level is not predictable within an individual or between individuals [ 16 ]. Dural perforation in a thick area of dura may be less likely to lead to a CSF leak than a perforation in a thin area, and may explain the unpredictable consequences of a dural perforation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cervical procedures can cause fatal complications. These complications include simple postoperative pain, vasovagal syncope, cerebrospinal fluid leakage, infection, epidural hematoma, pneumocephalus, spinal cord infarction, and direct spinal cord injury [9][10][11][12][13][14][38][39][40][41][42][43][44][45][46][47]. Most of them are caused by needle misplacement.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocephalus has been reported after traumatic injuries, spinal anesthesia and accidental dural puncture whilst performing epidural analgesia and epidural steroid injections. [3][4][5][6][7] However, there are only a few case reports that describe it after lumbar spine surgery. Akyüz et al described a case of delayed pneumocephalus and pneumorrhachis 2 months after lumbar spinal fusion surgery secondary to infection.…”
Section: Discussionmentioning
confidence: 99%